The Bride renewing our passion for the church - Swindoll, Charles R. 1934- (Grand Rapids, MI Zondervan, 1994)
Includes bibliographical references and index.
Originally published as "Rise and Shine" Portland OR.: Multnomah, c. 1989
Keywords: Mission of the church